Penerapan Strategi React Untuk Meningkatkan Pemahaman Siswa Pada Pembelajaran Matematika - Anisa Ul-Khoiriyah (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This research was conducted with the aim to determine students’ understanding of mathematics subjects when applied to the REACT strategy in the learning process. This study used classroom action research in class V of MI Al-Musdariyah Cileunyi Bandung which amounted to 24 students. Data collection techniques in this study used tests, observations, and documentation. Learning outcomes before using the REACT strategy were obtained 25% of the test results. Teacher activities in cycle I of action 1 and 2 were 50% and 66,67% increased in cycle II action 1 and 2 by 83,33% and 91,67%. Students activities in cycle I actions 1 and 2 amounted to 60,60% and 69,70%. There was an increase in cycle II of action 1 and 2 by 84,84% and 96,97%. The test result of students understanding using the REACT strategy increased, namely the first cycle of learning completeness classically, which was 74,98% and in the second cycle the classical learning completeness increased to 89,58%. It can be concluded that this REACT strategy can improve students understanding of mathematics subjects at MI Al-Musdariyah Cileunnyi.